Supercapacitance of core-shell hierarchical porous nitrogen-doped carbon in non-aqueous electrolyte. (June 2018) - Lu, Yun; Chen, Huamai; Ju, Xiaoxia; Xiang, Feng; Zhou, Ming
Graphical abstract: Highlights: The synthesized N-doped core-shell carbon has regular porous structure with high surface area and large pore volume. The N-doped carbon presents a capacitance of 352 F g –1 in 0.5 M H2 SO4 and a capacitance of 189.4 F g –1 in 1 M TEABF4 /ACN. The capacitance retention is 92% after 8000 repeating cycle tests. The improved performance is ascribed to the high surface area, large pore volume, well-defined mesopores and thin layer. The enhanced durability is resulted from higher graphitic structure, and better electrical conductivity. Abstract: Uniform nitrogen-doped carbon sphere with a 250 nm diameter macro hollow core and 75 nm thick shell structure containing 8 nm mesopores is synthesized from a silica hard template. The synthesized nitrogen doped hollow core mesoporous shell carbon (Fe-N-HCMS) presents excellent supercapacitor performance with a capacitance of 352 F g −1 (0.5 A g −1 ) in 0.5 M H2 SO4 and a capacitance of 189.4 F g −1 (0.5 A g −1 ) in 1 M TEABF4 /ACN. The capacitance retention of Fe-N-HCMS carbon is as high as 92% after tests of 8000 repeating cycles. The improved high-rate performance of Fe-N-HCMS carbon is ascribed to the high surface area (1788 m 2 g −1 ), large pore volume (3.98 cm 3 g −1 ), well-defined mesopores, leading to lower transport resistance and a thin diffusion layer. The enhanced durability of Fe-N-HCMS carbon also results from improved mechanical strength and better electrical conductivity with a higher graphitic content.